2021
DOI: 10.3389/fmicb.2021.687888
|View full text |Cite
|
Sign up to set email alerts
|

Thermonucleases Contribute to Staphylococcus aureus Biofilm Formation in Implant-Associated Infections–A Redundant and Complementary Story

Abstract: Biofilms formed by Staphylococcus aureus are one of the predominant causes of implant-associated infections (IAIs). Previous studies have found that S. aureus nucleases nuc1 and nuc2 modulate biofilm formation. In this study, we found low nuc1/nuc2 expression and high biofilm-forming ability among IAI isolates. Furthermore, in a mouse model of exogenous IAIs, Δnuc1/2 exhibited higher bacterial load on the surface of the implant than that exhibited by the other groups (WT, Δnuc1, and Δnuc2). Survival analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…Apparently, Nuc1 is important for S. aureus biomaterial-associated infection to persist in the acute phase of the foreign body reaction and even extends it, which was also indicated by the lack of foreign body giant cells in mice with the inoculated wildtype strain ( Table 1 ) corroborating earlier observations in biomaterial-associated infection studies ( van Putten et al., 2011 ; Sheikh et al., 2015 ). A recent study also showed that Nuc1 activity contributed to S. aureus survival in a hematogenous implant-associated infection model even though Nuc1 had no influence on the bacterial load in peri implant tissue or adherent bacteria on the implant and only nuc1 and nuc2 double mutants impacted bacterial load ( Yu et al., 2021 ). This discrepancy in the effect of Nuc1 on in-vivo bacterial survival may be due to differences in utilized clinical strain, inoculum concentration, site of implantation and type of biomaterial.…”
Section: Discussionmentioning
confidence: 99%
“…Apparently, Nuc1 is important for S. aureus biomaterial-associated infection to persist in the acute phase of the foreign body reaction and even extends it, which was also indicated by the lack of foreign body giant cells in mice with the inoculated wildtype strain ( Table 1 ) corroborating earlier observations in biomaterial-associated infection studies ( van Putten et al., 2011 ; Sheikh et al., 2015 ). A recent study also showed that Nuc1 activity contributed to S. aureus survival in a hematogenous implant-associated infection model even though Nuc1 had no influence on the bacterial load in peri implant tissue or adherent bacteria on the implant and only nuc1 and nuc2 double mutants impacted bacterial load ( Yu et al., 2021 ). This discrepancy in the effect of Nuc1 on in-vivo bacterial survival may be due to differences in utilized clinical strain, inoculum concentration, site of implantation and type of biomaterial.…”
Section: Discussionmentioning
confidence: 99%
“…The chromosome of S. aureus encodes thermonucleases, nuc gene. The nuc gene is known as a specific virulence factor in S. aureus [36], and it contributes to biofilm formation [37] and immune evasion [38].…”
Section: Discussionmentioning
confidence: 99%
“…However, NETs often fail to eradicate replicating S. aureus during persistent infections as this pathogen releases a plethora of virulence factors into the extracellular milieu that antagonize NET-mediated entrapment and killing ( Table 1 ) ( 79 ). For example, S. aureus secretes a robust thermonuclease (Nuc) which rapidly dismantles NETs thereby affecting local, systemic, as well as chronic infections ( Figure 1 ) ( 14 , 16 , 17 , 34 , 59 ). In that regard, we note that Nuc-mediated degradation of NETs may further restrict the communication of PMNs and macrophages ( 34 ).…”
Section: Staphylococcal Evasion From Net-mediated Entrapment and Killingmentioning
confidence: 99%